2011
DOI: 10.4149/neo_2011_05_449
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD147 in advanced non-small cell lung cancer correlated with cisplatin-based chemotherapy resistance

Abstract: CD147, a widely expressed cell surface glycoprotein in cancer, is associated with tumor invasiveness and chemotherapy resistance. Recently, CD147 is also regarded as a potential therapeutic target for cancer therapy. The aim of the study was to investigate CD147 expression in non-small cell lung cancer (NSCLC), and evaluate its correlation with cisplatin-based chemotherapy resistance. In this study, we examined immunohistochemically the expression of CD147 in 118 advanced NSCLC cases treated with cisplatin-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 0 publications
3
24
0
Order By: Relevance
“…In addition to inducing MMPs production, CD147 was shown to interact with integrins and CD147 participated in multiple cellular processes through integrin, such as modulating cell adhesion, invasion and angiogenesis . It was reported that membranous CD147 expression was a predictive factor of poor response to cisplatin‐based chemotherapies, and the use of CD147‐targeted therapeutic adjuvants might be considered in the treatment of patients with advanced in non‐small cell lung cancer and bladder cancer . Our study has proved that CD147 may represent an attractive target for immunotherapeutic approach in patients with tongue squamous cell carcinoma .…”
Section: Introductionsupporting
confidence: 59%
“…In addition to inducing MMPs production, CD147 was shown to interact with integrins and CD147 participated in multiple cellular processes through integrin, such as modulating cell adhesion, invasion and angiogenesis . It was reported that membranous CD147 expression was a predictive factor of poor response to cisplatin‐based chemotherapies, and the use of CD147‐targeted therapeutic adjuvants might be considered in the treatment of patients with advanced in non‐small cell lung cancer and bladder cancer . Our study has proved that CD147 may represent an attractive target for immunotherapeutic approach in patients with tongue squamous cell carcinoma .…”
Section: Introductionsupporting
confidence: 59%
“…18,26 Zeng et al have reported that CD147 membranous expression was associated with poor response to cisplatin-based chemotherapies and poor prognosis in advanced NSCLC patients. 27 Sienel et al have demonstrated that membranous localization of CD147 predicted prognosis of patients with operable lung AC. 28 In addition, Kaira et al have demonstrated that the positive CD98hc expression is a significant independent factor to predict poor prognosis in NSCLC patients.…”
Section: Discussionmentioning
confidence: 98%
“…There was also a decrease of monocarboxylate transporter 1 expression in the invasion and metastasis potential of pancreatic cancer cells, as well as increased chemosensitivity to gemcitabine in Panc-1 cells 47 . Membranous EMMPRIN expression, but not the overall EMMPRIN expression, was associated with poor response to cisplatin-based chemotherapies and a poor prognosis in advanced patients with non-small-cell lung carcinoma 48 . Silencing EMMPRIN increased the proliferation-inhibiting effect of cisplatin to lung cancer A549/DDP, 42 laryngeal carcinoma Hep2, 49 and gastric carcinoma SG7901 50 cells.…”
Section: Discussionmentioning
confidence: 96%